A paradigm shift for the treatment of hormone receptor-positive, human epidermal growth factor receptor 2-negative (HR+/HER2-) advanced breast cancer: a review of CDK inhibitors - Mariane Teodoro Fernandes; Jacob J Adashek; Carmelia Maria Noia Barreto; Ana Cláudia Barbin Spinosa; Barbara de Souza Gutierres; Gilberto Lopes; Auro del Giglio; Pedro Nazareth Aguiar Jr (BioExcel Publishing Ltd, 2018)
In the last 3 years, a novel class of targeted therapy has been approved for patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative (HR+/HER2-) breast cancer. There are currently three approved agents, which are oral cyclin-dependent kinase 4/6 (CDK4/6) inhibitors. All of the approved drugs exhibit progression-free survival benefit when compared to standard of care and generally have less adverse events compared to traditional chemotherapeutic options. The treatment of HR+/HER2- advanced breast cancer is a continuously evolving landscape, and the addition of CDK4/6 inhibitors is the newest mechanism for treatment. In this review, we summarize all available data, highlight the unanswered questions, and discuss pharmacological differences between each CDK4/6 inhibitor.